The efficacy and safety of antiviral drugs of direct action in liver recipients with recurrence of chronic hepatitis C genotype 1 after transplantation - О. M. Tsiroulnikova; D. V. Umrik; I. A. Miloserdov; Е. Т. Egorova; R. A. Latypov (Вестник трансплантологии и искусственных органов, 2019)
Aim. To study the efficacy and safety of the use of paritaprevir, ritonavir, ombitasvir and dasabuvir in combination or without ribavirin in liver recipients with recurrence of HCV 1 genotype after transplantation.Materials and methods. The study included 46 patients after orthotopic liver transplantation with recurrence of HCV 1 genotype. 37 patients completed a 24-week course of antiviral therapy, including paritaprevir, ritonavir, ombitasvir and dasabuvir in combination or without ribavirin. The effectiveness of the therapy was calculated as the proportion of patients who achieved aviremia 12 weeks after the end of the course of treatment. The safety of therapy was assessed by the number of adverse events that occurred during the course of antiviral therapy.Results. A sustained virologic response at 12 weeks after the end of the course of antiviral therapy, including paritaprevir, ritonavir, ombitasvir and dasabuvir, reached 100% of the recipients of the liver. Reduction in the intensity of cytolytic and cholestatic syndromes was noted at week 4 of therapy. Adverse events were recorded in 56.7% of the subjects, mostly they were not severe and were stopped on their own. Acute cellular rejection of the transplant developed in 1 patient (2.7%). There have been no cases of irreversible liver transplant dysfunction or death of the recipient.The conclusion. The use of paritaprevir, ritonavir, ombitasvir and dasabuvir is safe and effective in the treatment of relapse of HCV infection of 1 genotype after liver transplantation.